2005
DOI: 10.1042/bc20040122
|View full text |Cite
|
Sign up to set email alerts
|

Specific plasma membrane aquaporins of the PIP1 subfamily are expressed in sieve elements and guard cells

Abstract: Localization of the two abundant aquaporin isoforms suggests roles for specific PIPs of the PIP1 subgroup in phloem loading, transport and unloading, and in stomatal movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
49
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 52 publications
(77 reference statements)
6
49
2
1
Order By: Relevance
“…The target of the SE-specific antibody RS6, raised against the isolated SEs of Streptanthus tortuosus (Brassicaceae), was recently found in Arabidopsis to be an ENOD-like integral protein (Khan et al, 2007). Other proteins have been immunolocalized to SEs, such as the Suc-H 1 symporter SUT1 in potato (Solanum tuberosum; Kü hn et al, 1997), a putative monosaccharide transporter and a protonATPase in developing apple (Malus domestica) fruit (Zhang et al, 2004), a proton-amino acid transporter in Arabidopsis roots (Okumoto et al, 2004), a calcium channel-like protein in tobacco and Pistia stratiotes leaves (Volk and Franceschi, 2000), and a plasma membrane aquaporin in spinach (Spinacia oleracea; Fraysse et al, 2005).…”
Section: Expression Of the Sumcr Construct Yields An Mcitrine Signal mentioning
confidence: 99%
See 1 more Smart Citation
“…The target of the SE-specific antibody RS6, raised against the isolated SEs of Streptanthus tortuosus (Brassicaceae), was recently found in Arabidopsis to be an ENOD-like integral protein (Khan et al, 2007). Other proteins have been immunolocalized to SEs, such as the Suc-H 1 symporter SUT1 in potato (Solanum tuberosum; Kü hn et al, 1997), a putative monosaccharide transporter and a protonATPase in developing apple (Malus domestica) fruit (Zhang et al, 2004), a proton-amino acid transporter in Arabidopsis roots (Okumoto et al, 2004), a calcium channel-like protein in tobacco and Pistia stratiotes leaves (Volk and Franceschi, 2000), and a plasma membrane aquaporin in spinach (Spinacia oleracea; Fraysse et al, 2005).…”
Section: Expression Of the Sumcr Construct Yields An Mcitrine Signal mentioning
confidence: 99%
“…The strong CC-specific promoter AtSUC2p (Truernit and Sauer, 1995;Imlau et al, 1999) was used to drive FP fusions (Cutler et al, 2000) of proteins that are known to be targeted to plasma membranes (PIP subfamily of aquaporins; Fraysse et al, 2005) or are potentially small enough to sneak through the plasmodesmata as an FP fusion (AtRCI2A and AtRCI2B; Medina et al, 2001;Nylander et al, 2001). N-terminal FP fusions were employed to avoid interruption of potentially important 3#-signaling sequences in the mature mRNA, and a monomeric, environmentally stable form of yellow fluorescent protein (YFP; mCitrine) was used to avoid FP dimerization (Griesbeck et al, 2001;Zacharias et al, 2002).…”
mentioning
confidence: 99%
“…Antisense inhibition experiments on Arabidopsis thaliana PIP1 and PIP2 have suggested that the two subgroups of aquaporins contribute to root or leaf hydraulic conductivity in the same way (13). In several plant species, members of the PIP1 and PIP2 subgroups were shown to be coexpressed in the same cell type (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…However, it has remained unclear whether the accompanying water flow across the guard cell plasma membrane and tonoplast can simply be mediated by the lipid phase of membranes or whether aquaporins, channel proteins that facilitate transmembrane water transport, are involved. In fact, information on aquaporin expression in guard cells has remained scarce (Sarda et al, 1997;Sun et al, 2001;Fraysse et al, 2005;Shope and Mott, 2006;Yang et al, 2006;Heinen et al, 2014). Plasma membrane intrinsic proteins (PIPs) represent the most abundant aquaporins in the plant plasma membrane (Santoni et al, 2003), and transcriptome analysis indicated expression of 8 and 12 PIP isoforms in stomata of Arabidopsis thaliana and stomatal complexes of maize (Zea mays), respectively (Leonhardt et al, 2004;Heinen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%